Game-based rhythmic gymnastics exercise models to develop gross motor skills for primary school students - Fajar Sri Wahyuniati; M Furqon Hidayatullah; Sapta Kunta Purnama; Siswantoyo Siswantoyo; Tomoliyus Tomoliyus (Jurnal Cakrawala Pendidikan, 2023)
This research aims to develop game-based rhythmic gymnastics exercise models for primary school students, who have rhythmic gymnastics as a compulsory program in their curriculum. The sequential mixed method was employed to evaluate the exercise model. The data were analyzed using thematic qualitative analysis and expert’s judgement, in which the latter was designed to incorporate quantitative data. The experts in this research included 7 experts who are either academic instructors or professionals. Delphi method was used to collect the data and a Likert-scale questionnaire with a range of 1 to 4 was also employed along with Aiken's formula. This research formulated three models of rhythmic gymnastics exercise from the document analysis stage which include a jump exercise model with a seven-post circuit, pivot exercise model with a three-post circuit, and balance exercise model with a six-post circuit. Following the experts’ judgements, the models for jump, pivot, and balance games were considered to be excellent models for potential implementation in primary schools